Relationship between adherence to daily nicotine patch use and treatment efficacy: Secondary analysis of a 10 week randomized, double-blind, placebo-controlled clinical trial simulating over-the-counter use in adult smokers - Shiffman, Saul; Sweeney, Christine T.; Ferguson, Stuart G.; Sembower, Mark A.; Gitchell, Joseph G. (Clinical therapeutics, 2008)
Background: It has been reported that the efficacy of acute forms of nicotine replacement therapy, such as nicotine gum and lozenges, improves when sufficient quantities of medication are used. Objective: This analysis examined whether adherence with daily nicotine patch wear was associated with improved rates of smoking abstinence. Methods: This was a secondary analysis of data from a double-blind study in which subjects were randomized to receive either an active nicotine patch or a placebo patch under simulated over-the-counter conditions. Subjects were asked to complete a daily diary on their patch use and smoking. Logistic regression, controlling for smoking in the first 3 weeks of treatment, was used to evaluate the likelihood of abstinence at 6 weeks as a function of treatment assignment (active vs placebo) and adherence (ie, patch wear for ≥20 of the first 21 days of treatment). The relationship between reported adverse events and adherence was also examined. Results: This analysis involved data from 371 subjects, 204 using the active patch and 167 using the placebo patch. The study population was mainly white (87.3%), had a mean age of 42.8 years, a mean weight of 77.3 kg, had been smoking for a mean of 24.4 years, and smoked a mean of 25.2 cigarettes per day. Two hundred fifty-three subjects were classified as adherent. Rates of adherence did not differ significantly between the active and placebo groups (139 [68.1%] and 114 [68.3%], respectively). The likelihood of experiencing an adverse event did not differ significantly between adherent and nonadherent subjects in either group. Among active patch users, 61.5% of nonadherent subjects experienced an adverse event, compared with 59.7% of adherent subjects; among placebo patch users, the corresponding proportions were 41.5% and 43.9%. Among active patch users, the odds of abstinence at 6 weeks were more than 3 times greater for adherent versus nonadherent subjects (53.2% vs 21.5%, respectively; adjusted odds ratio [OR] = 3.25; 95% CI, 1.30-8.09; P = 0.011); no benefit of adherence over nonadherence was seen among users of the placebo patch (16.7% vs 15.1%; adjusted OR = 0.60; 95% CI, 0.16-2.31). The interaction between treatment group and adherence was statistically significant (P = 0.022). Conclusion: Under conditions simulating over-thecounter use, adherence to daily nicotine patch wear within the first 3 weeks of treatment was associated with an improved likelihood of achieving smoking abstinence at 6 weeks.